(untitled) (Revista Posgrado y Sociedad, 2020)
The main objective of the investigation was to understand the way in which women deprived of liberty of the Vilma Curling Rivera Institutional Care Center are affected, following the information published by the Costa Rican written press about their own judicial cases. For this, a qualitative, exploratory and descriptive approach methodology was used for the collection of information and to generate the exchange of opinions among the incarcerated population, based on the experiences they had with the written media. Due to the absence of similar research, this study seeks to provide theoretical and practical contributions to information coverage regarding women deprived of liberty, from the perspective of a journalism that fulfills its social function. Conclusions point to the need to establish in the country the figure of the Ombudsman - as did the Japanese newspaper Asahi Shimbun in 1992 - in order to guarantee social journalism, as well as the importance of carrying out training and awareness processes. for the journalistic approach, in order to contribute to a true reintegration of those women into society, avoiding stereotypes, stigmas and social labels that affect its development.